1972
DOI: 10.1346/ccmn.1972.0200304
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Base Interactions and the Properties of Kaolinite in Non-Aqueous Media

Abstract: Abstract--In non-aqueous systems, kaolinite can show, in addition to the physical interactions, considerable chemical activity. This study considers the chemical reactions that can occur at the kaolinite surface and explains these reactions in terms of acid-base interactions. In certain applications the chemical activity must be controlled if satisfactory products are to be obtained; for example, when kaolinite is used as a filler in rubber or as a diluent for insecticide powders. The concept of acid-base inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…By comparing our results with those given in the literature (Benesi, 1956(Benesi, , 1957Hirschler et al, 1961;Bailey et alo 1968;Solomon et al, 1971Solomon et al, , 1972 it can be seen that there is disagreement in the region of the strongly acidic sites. While the literature reports acid sites in montmorillonite corresponding to pKa values of -5"6 and -8'2 (i.e.…”
Section: Surface Acidity Measurementssupporting
confidence: 64%
See 1 more Smart Citation
“…By comparing our results with those given in the literature (Benesi, 1956(Benesi, , 1957Hirschler et al, 1961;Bailey et alo 1968;Solomon et al, 1971Solomon et al, , 1972 it can be seen that there is disagreement in the region of the strongly acidic sites. While the literature reports acid sites in montmorillonite corresponding to pKa values of -5"6 and -8'2 (i.e.…”
Section: Surface Acidity Measurementssupporting
confidence: 64%
“…It must also be established that there is no steric effect which will prevent the reactant from reaching some of the acid sites. According to Solomon et al (1972), such steric effects do.occur. Edge sites, though catalitically active, account for only a minor amount of the total acidity.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…For the other aluminosilicate samples, the acidity of unit surface area varied in the following order: Kaol-R > Hdm-R > Bent-J = R-Kaol-J > Zeol-J = Pal-R > W-Kaol-J > H-ZSM-5 = Diat-J. This is in agreement with the confirmed fact of an extremely high acidity of thermally treated Kaol, acidic surface of which at 0% moisture is equivalent in acidity to a solution of 90% sulfuric acid [14]. Additionally, as confirmed by Liu et al [56], the major acidic sites on the edges of minerals particles are ≡Si-OH and ≡Al-OH 2 OH groups, which had pK a s of 6.9 and 5.7 for kaolinite and pK a s of 7.0 and 8.3 for montmorillonite (Mt), respectively.…”
Section: Samplesupporting
confidence: 81%
“…Additionally, there is a good and proved opportunity for chemisorptions due to a stronger interaction between the surface and the molecules followed by formation of chemical bonds [12,13]. Of course, ion-exchange reactions (involving exchangeable cations or OH groups) are important and will readily contribute to the adsorption process, as well as catalytic ability in specific processes and conditions [14]. However, to be competitive to the other commercial materials and adsorbents, clay minerals should meet the same requirements as for other adsorbents (Table 1).…”
Section: Clays Clay Minerals and Ceramic Materials Based On Clay Minmentioning
confidence: 99%
“…Water has a relatively strong basic character, as indicated by its tendency to form hydrogen bonds and its relatively high autoprotolysis constant. Likewise, DMF has significant basic character due to the presence of two basic centers (Tahoun and Mortland, 1966 ,oo,oo,,r.o Harter and Ahlrichs (1969), Mortland (1968), Mortland and Raman (1968), Solomon andMurray (1972), andFrenkel (1974) showed that surface acidity increases as the degree of surface hydration decreases. Mortland and Raman (1968) proposed a mechanism by which the degree of polarization of remaining H20 of hydration and the resultant surface acidity increase with decreasing H20 content.…”
Section: Resultsmentioning
confidence: 99%